Hypertrophic obstructive cardiomyopathy and its outcome following surgical myectomy: a retrospective study - Gopalan, Vedanth; Bhandari, Pavaneel; Takalkar, Anant A. (International Surgery Journal, 2020)
Background: Hypertrophic cardiomyopathy is highly heterogeneous with a diverse anatomy, pathophysiology, and clinical course. It is obstruction to left ventricular outflow that has become the major hallmark of the disease. Septal myectomy has been the gold standard treatment for the relief of left ventricular outflow tract obstruction and cardiac symptoms in both adults and children with obstructive hypertrophic cardiomyopathy. Objective of the study was to evaluate effect of Myomectomy and its impact on survival for a period of one year. Methods: The study design is a retrospective record based observational study. Data was retrieved from previous records both electronic as well as manual records of all the patients who underwent myectomy with or without concomitant procedures such as mitral valve replacement or aortic valve replacement or coronary artery bypass surgery during 2014 to 2018. Results: Majority of the patients 11 (52.4%) in fourth decade i.e. 40-59 years age group. majority were males i.e. 16 (76.2%) and remaining 5 i.e. 23.8% were females. Male to female ratio was 3.2:1. Dyspnoea was present 81% and chest pain in 76.2%. Preoperative LVOT gradient was 86.86±20.33 and post-operative gradient was 23.47±20.49. Conclusions: Operative techniques have evolved from simple myotomy to the present method of extended septal myectomy which can be done in all adult cases of hypertrophic obstructive cardiomyopathy.